Trauma‐Informed Approaches to Juvenile Justice: A Critical Race Perspective. (February 2016) - Crosby, Shantel D.
Abstract: Youth of color experience disproportionate juvenile justice contact and recidivism. Trauma‐informed approaches may provide important support to these youth and improve their future outcomes. This paper describes dynamics of the various levels of the juvenile justice system (i.e., police contact, courts, correctional placement, aftercare) that perpetuate psychological trauma among adjudicated youth of color. This paper explores trauma‐informed approaches from a critical race theory perspective to address issues of systemic racial injustice in the juvenile justice system. Current and emerging models for trauma‐informed juvenile justice and implications for practice, policy, and research are discussed.